PEMANFAATAN SUMBER BELAJAR LINGKUNGAN SEKITAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA TEMA 6 (PANAS DAN PERPINDAHANYA) SUBTEMA 2 DI KELAS V MI. THORIQUL HUDA BATU - Sayyidatuna Intan Mahmudah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Abstract This study aims to : 1) describe the use of the environment as a learning resource, 2) determine the type of environment as a learningresource tahta can be used, and 3)determine the constrains faced in the implementation of the use of learning resource. Sumbject were pengampu teaching sciens as much as one person, and the five grade students as many as 35 students. Method of data collection using interviews, obsrvation, and dokumentation. Technique authenticity of data obtainedusing the technique of triangulation of source and method. Dara were analyzed using gualitative descriptive analysis. The result showed that 1)use of the enfironment as asource of learning done varied is a learning process inside and outside calssroom 2) the type of environment as a learning resource that can be used are school garden, sun shine, and environment around the school. 3) the constrains in implementing the learning by usingthe environment as a learning resource that teacher are less able to condition student, requires a lot of time in the process of implementation, summarizes the result of syudents’ difficulties in learning resources are limited in the neighborhood school.Keyword: Utilization of the Environment, Learning Resources, Science